2021
DOI: 10.1016/j.bmc.2021.116415
|View full text |Cite
|
Sign up to set email alerts
|

A short survey of dengue protease inhibitor development in the past 6 years (2015–2020) with an emphasis on similarities between DENV and SARS-CoV-2 proteases

Abstract: Dengue remains a disease of significant concern, responsible for nearly half of all arthropod-borne disease cases across the globe. Due to the lack of potent and targeted therapeutics, palliative treatment and the adoption of preventive measures remain the only available options. Compounding the problem further, the failure of the only dengue vaccine, Dengvaxia®, also delivered a significant blow to any hopes for the treatment of dengue fever. However, the success of Human Immuno-deficiency Virus (HIV) and Hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…Against the dengue virus, baicalein and baicalin (DENV). By eliminating extracellular viral particles, they prevented the growth of DENV-2.Baicalein demonstrated a strong affinity for the DENV NS3/NS2B protein (À7.5 kcal/mol) and the NS5 protein (À8.6 kcal/mol), according to in silico studies [198][199][200][201]. Baicalin may prevent CHIKV infection because of its high binding affinity (À9.8 kcal/mol) for the CHIKV nsP3 protein.…”
Section: The Antiviral Role Of Flavonoids Against Various Types Of Virusmentioning
confidence: 99%
“…Against the dengue virus, baicalein and baicalin (DENV). By eliminating extracellular viral particles, they prevented the growth of DENV-2.Baicalein demonstrated a strong affinity for the DENV NS3/NS2B protein (À7.5 kcal/mol) and the NS5 protein (À8.6 kcal/mol), according to in silico studies [198][199][200][201]. Baicalin may prevent CHIKV infection because of its high binding affinity (À9.8 kcal/mol) for the CHIKV nsP3 protein.…”
Section: The Antiviral Role Of Flavonoids Against Various Types Of Virusmentioning
confidence: 99%
“…Their genomes are composed of a single-stranded RNA, encoding a single polyprotein that acts as a precursor to other viral proteins. A two-component viral protease, NS2B-NS3, is a serine protease formed from the non-structural protein NS3 and the NS2B co-factor, that cleaves the precursor polyprotein into individual proteins required for viral replication [ 43 , 44 ]. This protease belongs to the trypsin superfamily with a preference for substrates with dibasic residues, such as arginine and lysine, and its active site contains a highly conserved catalytic triad composed of His51, Asp75 and Ser135 residues [ 45 , 46 , 47 ].…”
Section: Inhibition Of Viral Proteases By Targeting the Active Sitementioning
confidence: 99%
“…However, experimentally validated anti-dengue compounds were not comprehensively explored against SARS-CoV-2 M pro . In recent work, Murtuja et al demonstrated the development of DENV inhibitors with a targeted comparison of a protease between DENV and SARS-CoV-2 [ 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, experimental findings of inhibitors were also validated using molecular dynamics simulation to understand the molecular level interaction between proteins and small molecules [54]. Among natural compounds or their derivatives, flavonoid compounds were extensively used in various computation screening studies against M pro [55][56][57][58][59][60][61][62]. Many antiviral compounds were evaluated computationally against SARS CoV-2 M pro to detect their repurposing effect.…”
Section: Introductionmentioning
confidence: 99%